2007
DOI: 10.1093/jac/dkm340
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and characterization of integrons from bacteria isolated from a slaughterhouse wastewater treatment plant

Abstract: Our data support the hypothesis that WWTPs constitute a potential hot spot for horizontal gene transfer and for selection of antimicrobial resistance genes among aquatic bacteria. Moreover, water discharges represent a possible risk for dissemination of undesirable genetic traits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
101
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(112 citation statements)
references
References 28 publications
10
101
0
1
Order By: Relevance
“…Huys et al [25] and Rhodes et al [26] found more than 85% bacteria of the genus Aeromonas to be oxytetracycline-resistant. In this study, relatively large populations of Enterobacteriaceae microorganisms were reported in both, TET R and OTC R isolates, and similar observations were made by Guillaume et al [27] and Moura et al [28]. A comparison of MIC values and multiple drug resistance of the least resistant TET R isolates in samples of untreated and treated wastewater indicates a drop in resistance to tetracycline, oxytetracycline and a decrease in multiple drug resistance as a result of sewage treatment.…”
Section: Discussionsupporting
confidence: 88%
“…Huys et al [25] and Rhodes et al [26] found more than 85% bacteria of the genus Aeromonas to be oxytetracycline-resistant. In this study, relatively large populations of Enterobacteriaceae microorganisms were reported in both, TET R and OTC R isolates, and similar observations were made by Guillaume et al [27] and Moura et al [28]. A comparison of MIC values and multiple drug resistance of the least resistant TET R isolates in samples of untreated and treated wastewater indicates a drop in resistance to tetracycline, oxytetracycline and a decrease in multiple drug resistance as a result of sewage treatment.…”
Section: Discussionsupporting
confidence: 88%
“…One isolate, obtained from the mouth of the VR, harbored both classes of integrons, with gene cassette arrays: dfrA1-aadA1 (class 1 integron) and estX-sat2 (class 2 integron). Similar patterns were detected in Aeromonas and Enterobacteriaceae strains isolated from slaughterhouse WWTP (Moura et al 2007), in E. coli of human and animal …”
Section: Class 1 and 2 Integrons In Antimicrobial-resistant E Colisupporting
confidence: 74%
“…Overall, among 51 isolates, the overall mean transfer frequencies were Other investigations have demonstrated a transfer frequency at 10 ¡4 to 10 ¡2 transconjugants per recipient CFU of integron-harboring multi-drug-resistant Enterobacteriaceae isolated from clinical settings. 19 Different results, however, were observed by Moura et al 20 in which the frequency was one to 3 orders of magnitude lower at 3.79 £ 10 ¡5 and 5.46 £ 10…”
Section: Resultsmentioning
confidence: 81%
“…Single colonies were inoculated into 10 mL of selective LB broth (Mobio, Carlsbad, California) containing antibiotic(s) similar to LB agar plates which were incubated overnight at 37 C with shaking at 150 rpm. Conjugation assays were performed using a modification of the protocol in Moura et al 20 Donor and recipient cells were incubated separately overnight at 37 C with shaking at 165 rpm in liquid culture containing 5 mL LB broth. Donor and recipient cells were spread and enumerated using plate count assay on Mueller-Hinton (MH) agar before both cells were mixed in ratio of 1:1 and precipitated by centrifugation at room temperature for 5 min at 6700 g. Supernatants were removed and replaced by 1 mL fresh LB followed by incubation at 28 C for 24 h without shaking.…”
Section: Donormentioning
confidence: 99%